Հրաչյա Ղափլանյանի բեմադրությունները Երևանի Պատանի հանդիսատեսի թատրոնում - Առաքելյան, Ռուզաննա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Известный армянский режиссер и театральный деятель Грачья Капланян начал свою творческую деятельность в ереванском Театре юного зрителя, на сцене которого им было поставлено двадцать восемь спектаклей. Свою режиссерскую деятельность он начинал в качестве ассистента выдающегося театрального деятеля Тиграна Шамирханяна, что во многом способствовало его профессиональному росту. Спектакли, поставленные Грачья Капланяном в ТЮЗ-е, вписали новую страницу в летопись армянского театрального искусства. Эти спектакли производили неизгладимое впечатление как на юных, так и взрослых зрителей. Armenian theatre director and theatrical organizer Hrachya Ghaplanyan (1923–1988) started his creative activities at the Theatre of the Young Spectator and produced 28 stage productions. He worked as an assistant with the prominent theatre figure Tigran Shamirkhanyan, and this greatly enhanced his professional growth. The plays he staged at the Theatre of the Young Spectator wrote a new page in the annals of Armenian theatrical art and were highly appreciated by distinguished artists and theatre experts of the time. The audiences of both young and adult viewers were greatly impressed by his amazing creative stage productions.
Keywords: Արվեստագիտություն